PHYTOCHEMICAL EVALUATION AND QUANTIFICATION OF PRIMARY METABOLITES OF ALANGIUM SALVIIFOLIUM - BABEET SINGH TANWER,; REKHA VIJAYVERGIA, (International Journal of Pharma and Bio Sciences, 2010)
The use of traditional medicines and medicinal plants in most developing countries, as a normative basis for the maintenance of good health, has been widely observed. Laboratory evolutions were made to assess the phytochemical screening and quantification of primary metabolites in Alangium salviifolium. It contains higher soluble sugars in leaves, starch in stem, lipid in stem, phenol in leaves as compared to other parts of the plant. Maximum extractive value (4.130%) was found in water extract among test solvents. All the metabolites were qualitatively present in water and ethanolic extracts.